2019
DOI: 10.3389/fendo.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency in Overweight and Obese Children and Adolescents

Abstract: Excessive body weight and obesity in childhood and adolescence are becoming more and more important unfavorable factors that entail extremely adverse consequences and require close attention of physicians of any specialty. Along with the high prevalence of obesity and metabolic syndrome in pediatric patients, children and adolescents in the majority of countries are diagnosed with vitamin D deficiency. Among the non-calcaemic effects of vitamin D, a significant role is played by its impact on the hormonal regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
138
7
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(161 citation statements)
references
References 107 publications
4
138
7
4
Order By: Relevance
“…Reduced levels of circulating 25-hydroxyvitamin D (25-OHD), which is pivotal for bone health and accrual, have been often reported in children with obesity as compared to normal weight peers. On purpose, we will not discuss this issue, which has been the focus of a number of recent excellent reviews (173)(174)(175). We will focus on the link between dietary fatty acids (FAs) and bone metabolism.…”
Section: Emerging Dietary Issues: Polyunsaturated Fatty Acids and Polmentioning
confidence: 99%
“…Reduced levels of circulating 25-hydroxyvitamin D (25-OHD), which is pivotal for bone health and accrual, have been often reported in children with obesity as compared to normal weight peers. On purpose, we will not discuss this issue, which has been the focus of a number of recent excellent reviews (173)(174)(175). We will focus on the link between dietary fatty acids (FAs) and bone metabolism.…”
Section: Emerging Dietary Issues: Polyunsaturated Fatty Acids and Polmentioning
confidence: 99%
“…Interestingly, in diabetes, vitamin D supplementation promotes insulin secretion [ 80 , 141 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. Indeed, 25(OH)D levels are typically lower in obese individuals who are more likely to develop diabetes mellitus and metabolic syndromes [ 165 , 166 , 167 , 168 ].…”
Section: Vitamin D: State Of the Artmentioning
confidence: 99%
“…In addition, our results revealed that vitamin D de cient cases have signi cantly higher weight than patients with vitamin D levels above 20 ng/dl that is consistent with the result of studies reporting higher frequency of vitamin D de ciency in overweight and obese children and adolescents. (17) Several mechanisms have been described for the relation between vitamin D de ciency and increment in the risk for cardiovascular diseases (CVD). Low levels of vitamin D are believed to contribute to a rise in blood pressure.…”
Section: Discussionmentioning
confidence: 99%